Heterotic responses among crosses of IITA and CIMMYT early white maize inbred lines under multiple stress environments - Badu-Apraku, Baffour; Fakorede, M.A.B.; Gedil, Melaku A; Talabi, A.O.; Annor, B.; Oyekunle, M.; Akinwale, R.; Fasanmade, Y.; Akaogu, I.C.; Aderounmu, M. (Springer, 2015)
Two major constraintsmilitatingagainst the achievement of food security in West Africa (WA) are recurrent drought and poor soil fertility. Seventeen early maturing maize inbreds from IITA and CIMMYT were used as parents to produce 136 diallel crosses which were evaluated along with four checks in contrasting environments atfour locations for 2 year in Nigeria. The objectives of the study were to (i) examine the combin- ing ability of the lines under drought, low soil nitrogen (low N), optimal and across environments; (ii) classify the inbreds into heterotic groups using the specific combining ability (SCA) effects of grain yield, heterotic group’s specific and general combining ability (HSGCA), the heterotic grouping based on general combining ability (GCA) of multiple traits (HGCAMT) and the molecular-based genetic distance methods; (iii) compare the efficiencies of the four heterotic grouping methods in classifying the inbreds and identifying the best testers; and (iv) examine the performance of the inbreds in hybrid combinations across environments. Sum of squares for GCA of inbreds for grain yield and other measured traits were larger than those of the SCA in all environments. The relative importance of GCA to SCA effects for grain yield and other traits increased from stress to nonstress environments with the additive genetic effects accounting for the major portion of the total genetic variation under all research environments. The HSGCA method classified the lines into three groups and was the most efficient because it had the highest breeding efficiency (40 %) in the test environ- ments followed by the HGCAMT, SNP marker-based and the SCA effectsofgrain yieldmethods. Inbred TZEI 19 was identified as the best tester across research environments based on HSGCA method. Hybrids ENT 11 9 TZEI 19 and TZEI 1 9 TZEI 19 were the most outstanding and should be tested extensively in on-farm trials and commercialized.